The influence factors and perceptions towards the student performances and the tendency to choose public relations course / Siti Nirmala Mohamad Ishak - Mohamad Ishak, Siti Nirmala (Faculty of Communication and Media Studies, 2018)
This research examined the study of factors and perceptions towards the student's school and academic performances and their tendency to choose Public Relations course as the main options. The amount of survey c31culated based on Krejcie and Morgan Table, N=95 , 5=76 by using purposive sampling method. Descriptive quantitative research study was conducted through survey using questionnaire form. The independent variables involved are divided into two main dimensions which are factors and perceptions. There were three main factors; (1) Motivation Factor, (2) Family and Education Background and (3) Self-Interest. In the perceptions dimension included (1) Course and Assessment Content, and (2) Industry Prospect. The dependent variable studied the student's and academic performances that influence their decision making to choose their interested course. The suitable research theory that implemented throughout the study is Reasoned Action Model Theory by Martin Fishbein and Icek Ajzen which indicated the study towards perceptions, belief and behavior (action). The theory is practically implemented on the decision making process. The hypothesis testing gained by using two different methods which indicated different result which are Pearson Correlation and Multiple Linear Regression. Based on the research by using Pearson Correlation method, the five listed null hypothesis is accepted based on the standardized significant values which is must be or less than p=O.05. However, based on Multiple Linear Regression method, there are two different reading which formed different results. The first result is based on Beta value which shown the most significant relationship between independent towards dependent variables. Thus, the result indicated Industry Prospect (B=O.234) is the strongest relationship towards dependent variables (academic performances). However, based on significant value in Coefficient Multiple Linear Regression analysis, the null hypothesis of self-interest (p=O.042) and industry prospect (p=O.037) is being accepted with significant value below than p=O.05.